Perioperative Chemotherapy on Survival in Patients With Upper Urinary Tract Urothelial Carcinoma Undergoing Nephroureterectomy: A Population-Based Study - Zhai, Ting-Shuai; Jin, Liang; Feng, Li-Ming; Zhou, Zhen; Liu, Xiang; Liu, Huan; Ma, Wei-Guo; Lu, Jing-Yi; Chen, Wei; Yao, Xu-Dong; Ye, Lin (Frontiers in Oncology, 2020)
Objectives To estimate the stage-specific impact of perioperative chemotherapy on survival for upper urinary tract urothelial carcinoma (UTUC) patients treated with nephroureterectomy (NU). Methods Overall, 7278 UTUC patients treated with NU from 2004 to 2015 were identified within the SEER database. Kaplan-Meier plots were used to elucidate overall survival (OS) and cancer-specific survival (CSS) rates. Multivariable Cox regression analyses were used to test the impact of chemotherapy on survival rates, after stratifying according to pathological stage. Results Chemotherapy was performed in 17.3% of patients, and in 5.7, 11.5, 25.4 and 51.3% of patients with respectively pT1, pT2, pT3 and pT4 disease (P < 0.001). In multivariable analyses, perioperative chemotherapy was associated with a lower OS in pT2 patients and a lower CSS in pT1 disease (both P < 0.05), while predisposed to a higher OS in pT3 and pT4 patients (both P < 0.01). Moreover, perioperative chemotherapy was prone to a higher OS or CSS in pN+ disease compared to no chemotherapy (both P < 0.01). Conclusion Perioperative chemotherapy was more frequently performed in locally advanced UTUC patients. The beneficial effect of chemotherapy on OS was evident in pT3/pT4 and pN+ patients. And a clear CSS benefit was observed in patients who received chemotherapy for pN+ UTUC. While, perioperative chemotherapy may reduce CSS for pT1 and OS for pT2 patients following NU.